Design and Development of Pedal Operated Roller Type Lac Scraper - Prasad, Niranjan; Panday, S K; Bhagat, M L; Kumar, K K (Journal of Agricultural Engineering, 2001)
Manual lac scraping is a very slow and tedious process. One person scrapes 5-10 kg of lac in a day. In order to increase the output and reduce the drudgery of lac growing farmers a simple pedal operated roller type lac scraper was designed and developed. One person operates the machine and scraps about 6 kg lac sticks in an hour with scraping efficiency of about 95%.